Characterization and Comparison of Postnatal Rat Meniscus Stem Cells at Different Developmental Stages. (22nd October 2019) - He, Shaoqi; Ruan, Dengfeng; Chen, Yangwu; Ran, Jisheng; Chen, Xiao; Yin, Zi; Tang, Chenqi; Huang, Jiayun; Heng, Boon Chin; Chen, Jialin; Chen, Weishan; Shen, Weiliang; et al.
Abstract: Meniscus-derived stem cells (MeSCs) are a potential cell source for meniscus tissue engineering. The stark morphological and structural changes of meniscus tissue during development indicate the complexity of MeSCs at different tissue regions and stages of development. In this study, we characterized and compared postnatal rat meniscus tissue and MeSCs at different tissue regions and stages of development. We observed that the rat meniscus tissue exhibited marked changes in tissue morphology during development, with day 7 being the most representative time point of different developmental stages. All rat MeSCs displayed typical stem cell characteristics. Rat MeSCs derived from day 7 inner meniscus tissue exhibited the highest self-renewal capacity, cell proliferation, differentiation potential toward various mesenchymal lineage and the highest expression levels of chondrogenic genes and proteins. Transplantation of rat MeSCs derived from day 7 inner meniscus tissue promoted neo-tissue formation and effectively protected joint surface cartilage in vivo. Our results demonstrated for the first time that rat MeSCs are not necessarily better at earlier developmental stages, and that rat MeSCs derived from day 7 inner meniscus tissue may be a superior cell source for effective meniscus regeneration and articular cartilage protection. This information could make a significant contribution to human meniscus tissue engineering in the future. Stem Cells Translational Medicine 2019;8:1318&1329 : Abstract : (A): Meniscus tissue at different tissue regions and stages of development. (B): MeSCs at different tissue regions and stages of development. (C): Intra-articular injection of MeSCs for meniscus regeneration and OA suppression. *Significant difference between two groups at p < .05. **Significant difference between two groups at p < .01. ***Significant difference between two groups at p < .001. ****Significant difference between two groups at p < .0001. N.S., No significant difference between two groups at p ≥ .05.